2016
DOI: 10.1007/s10964-016-0532-0
|View full text |Cite
|
Sign up to set email alerts
|

Considering Friends Within the Context of Peers in School for the Development of Ethnic/Racial Identity

Abstract: The importance of ethnicity/race for adolescents’ identity (i.e., centrality), and how that importance changes over time, may in part be a function of the social contexts that they inhabit. Although centrality has shown to be an adaptive component of ethnic/racial identity, little is known about how centrality changes during adolescence in relation to these social contexts. The current study examined the role of same-ethnic/racial peers and friends in the longitudinal development of ethnic/racial identity cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 45 publications
(63 reference statements)
0
16
0
Order By: Relevance
“…This might be especially relevant when studying cultural identity development and adjustment of recently migrated individuals in Europe. This study has shown once again that qualitative and person-centered approaches can add valuable insights into personal identity experiences of ethnic minority members while accounting for context and time (e.g., Douglass et al, 2016;Syed & Azmitia, 2010).…”
Section: Future Directions and Implicationsmentioning
confidence: 82%
See 1 more Smart Citation
“…This might be especially relevant when studying cultural identity development and adjustment of recently migrated individuals in Europe. This study has shown once again that qualitative and person-centered approaches can add valuable insights into personal identity experiences of ethnic minority members while accounting for context and time (e.g., Douglass et al, 2016;Syed & Azmitia, 2010).…”
Section: Future Directions and Implicationsmentioning
confidence: 82%
“…Treating diversity as a benefit and different cultural identities as equally important, these relational contexts offered a bigger variety of positive group identities for Turkish-heritage individuals to draw from. Importantly, a low ethnic group representation in school promoted participants' heritage culture exploration solely within multicultural relations outside of school (Bauer et al, 2013), which led to a stronger and more salient heritage identity in these relational contexts (Douglass, Mirpuri, & Yip, 2016;Juang & Nguyen, 2010). Thus, compatible cultural identities within multicultural environments and the possibility to belong helped buffer against feeling disconnected from either the dominant-or the heritage-culture group and thus may have lessened the negative effects of "cultural homelessness" (Navarrete & Jenkins, 2011).…”
Section: Constructing Cultural Identities Based On Relational Experiementioning
confidence: 99%
“…We did not find that school and neighborhood racial composition and intergroup contact strongly differentiated between the three profiles. A number of studies have shown how same‐race friends can support ERI (Douglass, Mirpuri, & Yip, 2017; Graham, Munniksma, & Juvonen, 2014; Kiang, Witkow, Baldelomar, & Fuligni, 2010; Phinney, Horenczyk, Liebkind, & Vedder, 2001a; Phinney, Romero, Nava, & Huang, 2001b), but these studies did not measure the aspects of climate (i.e., socialization messages) that might have an even stronger relation with outcomes. Specifically, it is likely not the mere presence of same‐race friends but the types of conversations that are had with those friends and the messages youth receive about those friendships that make the friendships meaningful for identity processes and content.…”
Section: Discussionmentioning
confidence: 99%
“…Schools are developmental contexts that influence academic adjustment in a variety of ways, including interactions with teachers and peers (Stewart, 2007; Thibodeaux, 2013). Studies of racial identity processes have included Black adolescent samples from a variety of demographic contexts, from schools in predominantly Black working-class communities (e.g., Chavous et al, 2003) to predominantly White middle-class suburban schools (e.g., Ispa-Landa & Conwell, 2014), to ethnically diverse schools (Chavous et al, 2008; Douglass, Mirpuri, & Yip, 2017; Yip, Seaton, & Sellers, 2010). While researchers often highlight the importance of considering context in interpreting their study findings, there has been little explicit consideration of how Black adolescents’ racial identity beliefs may function within differing demographic contexts (Hurd, Sellers, Cogburn, Butler-Barnes, & Zimmerman, 2013).…”
Section: Schools As Racialized Developmental Contextsmentioning
confidence: 99%